Marmoset Fine B Cell and T Cell Epitope Specificities Mapped onto a Homology Model of the Extracellular Domain of Human Myelin Oligodendrocyte Glycoprotein - Michael F. Mesleh; Nicole Belmar; Chuan Wei Lu; V.V. Krishnan; Robert S. Maxwell; Claude P. Genain; Monique Cosman (Neurobiology of Disease, 2002)
Aberrant association of autoantibodies with myelin oligodendrocyte glycoprotein (MOG), an integral membrane protein of the central nervous system (CNS) myelin, has been implicated in the pathogenesis of multiple sclerosis (MS). Sensitization of nonhuman primates (Callithrix jacchus marmosets) against the nonglycosylated, recombinant N-terminal domain of rat MOG (residues 1–125) reproduces an MS-like disease in which MOG-specific autoantibodies directly mediate demyelination. To assess the interrelationship between MOG structure and the induction of autoimmune CNS diseases and to enable structure-based rational design of therapeutics, a homology model of human MOG(2–120) was constructed based on consensus residues found in immunoglobulin superfamily variable-type proteins having known structures. Possible sites for posttranslational modifications and dimerization have also been identified and analyzed. The B cell and T cell epitopes have been identified in rat MOG-immunized marmosets, and these sequences are observed to map primarily onto accessible regions in the model, which may explain their ability to generate potent antibody responses.